Meta-analysis Study: Effect of Problem Solving Learning Model on Problem Solving Ability in Students' Science Learning SMP-SMA - Yayat Suharyat; Linda Winiasri; Tomi Apra Santosa; Abdul Rahman; Kartini Marzuki (Postgraduate, University of Mataram, 2023)
In the era of the industrial revolution 4.0, the education system has used technology to assist the learning process. Technology-based learning makes it easy for students and teachers to carry out learning activities. However, teachers have not been able to optimally develop students' potential, low student learning outcomes and low problem-solving abilities in students. Problem solving ability is very important for a student in learning science. Problem-solving skills in science learning are the main key to training students' scientific thinking in solving phenomena in science. So, it is necessary for a teacher to improve the learning model for those who are able to develop students' problem solving abilities. Problem solving learning is a learning model based on problem solving. In addition, the problem solving learning model helps teachers to be more creative in carrying out the teaching and learning process. This study aims to analyze the effect of problem solving learning models on students' problem solving abilities in science learning. The data source for this research comes from an analysis of 30 national or international journals that have been published from 2010-2022. The search for data sources came from the Google Scholar, ScienceDirect, Emerald, Eric, Springer, Hindawi, ProQuest, Sage Journal, Wiley and Taylor of Francis databases. Sampling in this study was carried out by using purposive sampling technique. The data that can be used is related to the research variable. Furthermore, the research data search keywords are problem solving learning models, problem solving skills and science learning. Data analysis is a descriptive quantitative analysis technique with the help of the OpenMEE application. The results of the study concluded that the problem solving learning model had a significant influence on students' problem solving abilities in science learning with an effect size of 1.808, an average value of 83 and a standard deviation of 0.45 Â